US International Equity Investment and Past and Prospective Returns - Curcuru, Stephanie E; Thomas, Charles P; Warnock, Francis E; Wongswan, Jon (American Economic Review, 2011)
Counter to extant stylized facts, using newly available data on country allocations in US investors' foreign equity portfolios we find that (i) US investors do not exhibit returns-chasing behavior, but, consistent with partial portfolio rebalancing, tend to sell past winners; and (ii) US investors increase portfolio weights on a country's equity market just prior to its strong performance, behavior inconsistent with an informational disadvantage. Over the past two decades, US investors' foreign equity portfolios outperformed a value-weighted foreign benchmark by 160 basis points per year. JEL: C58, G11, G15